Exploring social justice implications of mitigation policies :|positions of climate action advocates in Turkey - Yeniev, Gökçe. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2022., 2022)
Studies show that in the absence of corrective complementary social policies, environmental mitigation policies are very likely to fail to provide overall positive societal results. Although the challenges should be addressed to ensure a sustainable and equitable transition, so far scant attention has been directed to rebuilding the economy in a low-carbon and at the same time in a just manner, especially in the context of developing countries. Based on 21 in-depth interviews conducted with climate advocates in Turkey, the ways they address the impacts of mitigation policies on affordability, employment, equality, and social cohesion, as well as social policies they suggest offsetting the potentially-detrimental effects of mitigation policies are investigated. After reviewing briefly utilitarian, distributive, participatory, and capabilities approaches to environmental justice in the context of mitigation policies, the study proposes an analytical tool—by proposing a quadrant of justice—to map the corresponding justice approaches of various social measures recommended by climate advocates. The results of the study are as follows: a) Climate advocates consider the social impacts of low-carbon investments as relatively positive, while assessing the social risks of the policies that will impose sanctions on carbon-intensive industries as high; b) for the complementary social policies, climate advocates challenge the existing socio-economic structure when it comes to adopting a combination of different justice typologies; c) although the academic research on the social impacts of mitigation policies have increased quantitatively and qualitatively recently, the issue is not by and large on the agenda of climate advocates in Turkey.
Keywords: Turkey -- Social policy.; Climatic changes -- Government policy -- Turkey.; Sustainable development.